The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1177/1049732303259663
|View full text |Cite
|
Sign up to set email alerts
|

Surfacing the Life Phases of a Mental Health Support Group

Abstract: Support groups have increased rapidly in number and become a viable alternative to formal treatment in the United States. However, little is known regarding how mental health advocacy or support groups start and develop, or about challenges that can threaten their survival. In this 2 1/2-year ethnography, the author studied the culture of a developing family support program associated with a system of care. Several phases emerged, reflecting an organizational dynamic. The group dynamics and response to challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
0
28
0
4
Order By: Relevance
“…These roles include direct caring work as well as indirect contributions such as management and fundraising (Davis Smith 1998). Volunteers are often instrumental in setting up nonprofit groups (Mohr 2004) as well as in ''steady state' ' (McDonald and Warburton 2003). More broadly, volunteering is an indicator of social cohesion and civic engagement (Putnam 2000).…”
Section: Research Issuesmentioning
confidence: 99%
“…These roles include direct caring work as well as indirect contributions such as management and fundraising (Davis Smith 1998). Volunteers are often instrumental in setting up nonprofit groups (Mohr 2004) as well as in ''steady state' ' (McDonald and Warburton 2003). More broadly, volunteering is an indicator of social cohesion and civic engagement (Putnam 2000).…”
Section: Research Issuesmentioning
confidence: 99%
“…Thus, aside from some studies in which researchers used observation (King, Stewart, King, & Law, 2000;Middleton, 1996;Mohr, 2004), little is known about the patterns and interactional processes that characterize support group participation (Davison et al, 2000).…”
Section: Data Collection: the Ethnographic-discursive Approachmentioning
confidence: 99%
“…In much the same way, the current review found that relatively few studies examined the effects of peer-support self-help groups. Peer-support self-help groups are often thought to be synonymous with self-help approaches for mental health problems and have grown dramatically during the past several decades (Mohr, 2004;Wuthnow, 1994). However, due to a lack of studies, we were unable to compare their efficacy to other theoretical bases.…”
Section: Directions For Future Researchmentioning
confidence: 99%